Physical-topology modeling of silicon/gallium arsenide Schottky transistor of submicron technology LSI - Novosyadliy, S. P.; Lukovkin, V. M.; Melnyk, R.; Pavlyshyn, A. V. (Physics and Chemistry of Solid State, 2020)
In this paper described researched essentials and physical mechanisms of MESFET on epitaxy layers of GaAs with monocrystalline silicon wafer. Conducted computer modeling of MESFET with p-channel: distributions of potential, volumetric charge, current in channel and its characteristics. Based on conducted modeling discovered new effect in MESFET, shielding of volumetric charge, which sufficiently influences on current distribution in channel.